Physical Signs of Illness, Liver Functions and Reproductive Parameters of Female Rats Supplemented with Melaleuca cajuputi Methanolic Extract - Dzulsuhaimi Daud, Nur Lisma Ruhila Alias, Mohd Tajudin Mohd Ali, Alene Tawang (Journal of Applied Pharmaceutical Science, 2018)
Melaleuca cajuputi is the main source of cajuput essential oil, which is widely used in the folk medicine in southeastern Asia. The study aimed to determine the effect of M. cajuputi methanolic extract (MCME) on liver functions and fertility of female Sprague Dawley rats. Twenty four female rats were divided into four groups and supplemented with 2 ml/kg bwt distilled water or several doses of MCME (50, 100, and 200 mg/kg bwt) for 30 days. Physical signs of illness were observed on a daily basis. Blood was collected at the end of the experimental period for liver functions and estrogen assay. All females also subjected to fertility test. No signs of illness and mortality were observed. Results also demonstrated that liver functions, estrogen level and fertility in female Sprague Dawley rats were not affected by MCME. These findings suggested that MCME at doses in between 50-200 mg/kg bwt were not toxic to female Sprague Dawley rats.
Keywords: Melaleuca cajuputi, toxicity, liver functions, estrogen assay, in-vivo fertilization.